2015
DOI: 10.1007/s11738-015-1849-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth and development in phytochrome mutants of Arabidopsis thaliana by solar UV

Abstract: Phytochrome mutants (phyA, phyB and phyAB) of Arabidopsis thaliana were grown under ambient and UV-excluded sunlight to understand their influence on growth and development by mutual exclusion. Phytochrome A and B played a complementary role in the regulation of germination. Suppression of hypocotyl length was predominantly under the control of phytochrome B; UV photoreceptors were active in suppression of hypocotyl growth only in phyB and phyAB mutants. Exclusion of UV promoted the number and the area of rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Similar to the tolerance of phyB mutants to stress, as already discussed, UV-B radiation caused less deleterious effects on the growth of these genotypes as compared with WT. Mani and Guruprasad (2015) observed that when excluding the UV-B and UV-A spectra of sunlight using filters, WT had a greater biomass than Arabidopsis phyB and phyAB mutants, indicating the relationship between the UV receiver and the phytochrome B during growth under UV-B radiation. Moreover, the influence of negative control of phytochromes B1 and B2 in response to UV-B radiation in both length and root biomass ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the tolerance of phyB mutants to stress, as already discussed, UV-B radiation caused less deleterious effects on the growth of these genotypes as compared with WT. Mani and Guruprasad (2015) observed that when excluding the UV-B and UV-A spectra of sunlight using filters, WT had a greater biomass than Arabidopsis phyB and phyAB mutants, indicating the relationship between the UV receiver and the phytochrome B during growth under UV-B radiation. Moreover, the influence of negative control of phytochromes B1 and B2 in response to UV-B radiation in both length and root biomass ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of how phytochromes work at the molecular level, the identification of transcription factor families whose action is regulated by phytochromes (Castilon, 2007;Zheng et al, 2014) and the increased availability of phytochrome mutants in different plant species provide ideal tools for studying the participation of these photoreceptors in biotic and abiotic stress responses. With respect to the multitude of abiotic and biotic stresses modulated by phytochromes, they have been shown to be important components of plant signaling pathways involved in responses to insect herbivory (Ballaré, 2009;Howe and Jander, 2008), temperature fluctuations (Auge et al, 2012;Donohue et al, 2008;Foreman et al, 2011), harmful light radiation (e.g., ultraviolet B (UV-B)) (Boccalandro et al, 2001;Kreslavski et al, 2013Kreslavski et al, , 2015Mani and Guruprasad, 2015), salt stress (Balestrasse et al, 2008a;Datta et al, 2008), water stress (D'amico-Damião et al, 2015;Kidokoro et al, 2009) and even heavy metal intoxication . Because those environmental conditions can greatly affect plant productivity, the studies on phytochrome regulation of stress responses have become a hot spot of research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to red and far-red lights, the phytochromes are also able to absorb ultraviolet (UV) radiation. Exploring the functions of Arabidopsis PhyA and PhyB in plant response to UV-B light (280-315 nm) showed their regulatory roles in a broad range of biological processes, including hypocotyl elongation (negatively regulated by PhyB), germination, rosette growth (regulated by synergistic action of PhyA and PhyB), and biomass accumulation (regulated by PhyA, PhyB, and other phytochrome members) (104). Furthermore, the importance of these two phytochromes in controlling light-mediated photosynthesis and programmed cell death in response to UV-C light (200-280 nm) has also been demonstrated (130).…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…The value of R/FR ratio directly modifies the phytochrome properties, activating or inhibiting the shadow avoidance reaction (Franklin & Quail, 2010). Phytochrome also plays an important role in modulating signaling pathways during plant reactions to various abiotic stresses, including light stress (Mani & Guruprasad, 2015). Phytochrome-dependent photoprotective mechanisms are associated with the change in the structure and size of the LHCII pool.…”
Section: Introductionmentioning
confidence: 99%